Public Sector Crises: Realizations from Covid-19 for Crisis Communication - Coombs, W. Timothy (PARTECIPAZIONE E CONFLITTO, 2020)
This article reflects upon the communicative demands COVID-19 created for public sector crisis managers. Those demands include anxiety, empathy, efficacy, fatigue, reach, and threat. The conclusion reviews the realizations COVID-19 has created for those tasked with managing public health crises.